Development of the transcallosal motor fiber from the corticospinal tract in the human brain: diffusion tensor imaging study - Kwon, Hyeok Gyu; Son, Su Min; Jang, Sung Ho (Frontiers in Human Neuroscience, 2014)
Transcallosal motor fiber(TCMF) plays a role in interhemispheric inhibition(IHI) between two primary motor cortices. IHI has been an important concept in development of the motor system of the brain. Many studies have focused on the topography of TCMF, therefore, little is known about development of TCMF. In the current study, using diffusion tensor tractography, we attempted to investigate development of TCMF from the corticospinal tract (CST) in the human brain. A total of 76 healthy subjects were recruited for this study. We reconstructed the TCMF, which was derived from the CST, by selection of two regions of interest below the corpus callosum(upper and middle pons). Termination criteria used for fiber tracking were fractional anisotropy < 0.2 and three tract turning angles of < 45°, 60°, and 75°. The subjects were classified into four groups according to age: group A(0 to 5 years), group B(6 to 10 years), group C(11 to 15 years), and group D(16 to 20 years). Significant differences in the incidence of TCMF were observed between group B and group C, and between group B and group D, with tract turning angles of 60° and 75°(p< .05). However, no significant differences with any tract turning angle were observed between group C and group D (p>.05). In addition, in terms of the incidence of TCMF, no significant differences were observed between the three tract turning angles(p>.05). We obtained visualized TCMF from the CST with development and found that the incidence of TCMF differed significantly around the approximate age of 10 years. As a result, we demonstrated structural evidence for development of TCMF in the human brain.